The Influence of Carbon Tax on Green Economy: A Literature Analysis - Ikhtiari, Kirana; Nurfadila, Nurfadila; Ibrahim, Fifi Nurafifah (Advances in Taxation Research, 2024)
Purpose: This research examines the role of carbon taxes in advancing the green economy agenda, focusing on effectiveness, distributional implications, and policy implications. Research Design and Methodology: This study employs a qualitative literature review methodology by synthesizing existing scientific literature to explore diverse perspectives, theoretical frameworks, and empirical findings. The research formulated specific research questions to guide the literature review process, focusing on key themes such as the theoretical basis of carbon taxes, empirical evidence on their effectiveness, implementation challenges and barriers, and policy implications. Findings and Discussion: This study finds that carbon taxes effectively reduce carbon emissions and promote sustainable development, supported by empirical evidence and economic theory. However, the study also highlights the distributional implications and social justice considerations, emphasizing the need for targeted policy interventions to address social justice issues. Implications: This study's results emphasize the importance of integrating carbon pricing with complementary policies and institutional frameworks to enhance its effectiveness in achieving green economy goals.